2001
DOI: 10.1054/jhsb.2001.0590
|View full text |Cite
|
Sign up to set email alerts
|

The Mexican Hat Splint – A New Splint for the Treatment of Closed Mallet Finger

Abstract: A new splint for the treatment of closed mallet finger injuries is described. This is a modified aluminium-foam ('Zimmer') splint, which takes account of the skin circulation at the distal interphalangeal joint, and is specifically designed to alleviate the potential problems which can be seen with the traditional 'mallet finger' splints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…Goto et al found a final extension lag of 8.5 • and excellent or good results in 88% of patients, according to the criteria of Crawford [19]. Kalainov [22][23][24][25][26]. We believe our findings are reflective of the superior healing capacity of bone fractures compared with tendons, and the smaller DIP joint extensor lag observed following bony compared with tendinous mallet injuries.…”
Section: Discussionsupporting
confidence: 51%
“…Goto et al found a final extension lag of 8.5 • and excellent or good results in 88% of patients, according to the criteria of Crawford [19]. Kalainov [22][23][24][25][26]. We believe our findings are reflective of the superior healing capacity of bone fractures compared with tendons, and the smaller DIP joint extensor lag observed following bony compared with tendinous mallet injuries.…”
Section: Discussionsupporting
confidence: 51%
“…En 1969, Stack 35 presentó su férula corta, mejorada en 1986 36 , disminuyendo la maceración y liberando un poco el pulpejo. Posteriormente se desarrollaron un gran número de modelos 10,11,4,23,33,34,1,24,8,16,9,15,30,43,20 . Nosotros nos basamos en la descripción de Elliot 8 para la localización dorsal de la férula, liberando completamente el pulpejo.…”
Section: Discusionunclassified
“…For non-complicated cases some authors recommend conservative treatment, usually by splinting or casting [1][2][3][4][5]. Under some conditions, however, operation is much more preferred, as suggested by various published reports [6][7][8].…”
Section: Introductionmentioning
confidence: 99%